Malay young adults and internet television in Malaysia: an analysis of viewing habits and potential impact / Dzaa Imma Abdul Latiff ... [et al.] - Abdul Latiff, Dzaa Imma; Ismail, Siti Nasarah; Sah Allam, Siti Nur Shahida; Kamal, Suhaila; Radzi, Raha (2015)
The focus of this study is to investigate the viewing habits and potential impact among Malay young adults on Internet TV and how they accept this technology in their daily life. Since the late 1960s, television has developed from black and white pictures to high definition TV. Internet TV which offers online video streaming is becoming more popular nowadays where the TV programs are available through a computer screen, tablet or smartphone. New media technologies like Internet TV in Malaysia are relatively new and most studies are mainly focused on business and technology impact. Therefore, the objective of this study is to identify the viewing habits and how Internet TV used may affect people’s culture and lifestyle. A convenience sample of 111 final students from Universiti Teknologi MARA (UiTM), Melaka was used in this study. The study found that Malay students’ viewing habits and practices are slightly different compared to traditional TV used. The findings are also important to Broadcast TV station and Internet TV developers in order to develop effective medium in delivering efficient TV programs to target audience. The use of portable media able to change the course of human life no matter young or old. Internet TV in Malaysia is becoming a trend nowadays when every consumer of portable media can access to TV broadcasts via Internet without having to be at home. In addition, by knowing the viewing habits and knowledge about Internet TV may encourage researchers to investigate future media trend.